Impact on Mental Health Due to COVID-19 Pandemic: Cross-Sectional Study in Portugal and Brazil - Passos, Lígia (Int J Environ Res Public Health, 2020)
Mental health effects secondary to the COVID-19 pandemic were till recently considered less important or were neglected. Portugal and Brazil are facing the pandemic in quite different ways. This study aimed to describe the mental health status of the general adult population in Portugal and Brazil during the COVID-19 pandemic and analyze the differences between the two countries. A cross-sectional quantitative study was based on an online questionnaire. Socio-demographic data were collected in addition to four validated scales: CAGE (acronym cut-annoyed-guilty-eye) Questionnaire, Satisfaction with Life Scale, Generalized Anxiety Disorder-7 and Patient Health Questionnaire-2. For each outcome, a multiple linear regression was performed. Five hundred and fifty people answered the questionnaire (435 women). The median age was 38 (Q1, Q3: 30, 47) years, 52.5% resided in Brazil and 47.5% in Portugal. The prevalence of anxiety was 71.3% (mild anxiety was present in 43.1%), the prevalence of depression was 24.7% and 23.8% of the sample had both depression and anxiety. Isolation was a significant factor for depression but not for anxiety. Well-being was below average. Mental illness was considerably higher than pre-COVID-19 levels. Portugal and Brazil will have to be prepared for future consequences of poor mental health and contribute immediate psychological support to their adult populations.